New records of water mites mainly from Vogelkop, New Guinea (Acari: Hydrachnidia), with the description of one new genus and thirteen new species - Smit, Harry (Zootaxa, 2013)
New records are given of water mites from Vogelkop, New Guinea. A total of 33 species is recorded, including the des-criptions of a representative of a new genus, i.e. Dropursides aberratus, and of twelve further species new to science, i.e. Hydrobaumia purpurea, Oxus manokwariensis, Limnesia multiscutata, Limnesia vogelkop, Australiobates elongatus, Unionicola novaeguineae, Neumania silvestris, Recifella fluviatilis, Koenikea sentaniensis, Albia ilikensis, Albia papuaensis and Axonopsella bisetosa. The female of Albia wauensis Wiles and the male of Axonopsella ovalis Wiles are described for the first time.